TEACHING READING HORTATORY EXPOSITION TEXT BY USING GIVE ONE, GET ONE STRATEGY TO THE ELEVENTH GRADE STUDENTS OF SMAN 7 PALEMBANG - Zuria Kausari (Edukasi, 2016)
The objectives of this study are to find out whether or not there is a significant improvement before and after the treatment on the eleventh grade students’ reading comprehension scores of SMAN 7 Palembang by using Give One, Get One strategy and to find out whether or not there is a significant difference on the eleventh grade students’ reading comprehension scores of SMAN 7 Palembang between the students who are taught by using Give One, Get One strategy and those who are not. In this study, the researcher used Quasi Experimental Design using pretest-posttest nonequivalent groups design. There were 80 students taken as sample. Each class consisted of 40 students from class XI IPA 1 as experimental group and class XI IPA 2 as control group. In collecting the data, test was used. The test was given twice to experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The findings showed that the p-output from paired sample t-test (sig2-tailed) was 0.000 which was lower than 0.05 and t-value 11.955 was higher than t-table with df=39 (2.0227).  The result of p-output from independent sample t-test was 0.002 which was lower that 0.05 and the t-value 3.250 was higher than t-table with df=78 (1.9908). it means that teching reading hortatory exposition text by using Give One, Get One strategy had significant effect on the students’ reading comprehension scores.